KONTRIBUSI PENGUASAAN KALIMAT EFEKTIF TERHADAP KETERAMPILAN MENULIS TEKS EKSPOSISI SISWA KELAS X SMK NEGERI 2 PADANG - Citra, Diana; Afnita, Afnita (Universitas Negeri Padang, 2019)
ABSTRACT The purpose of this study was categorized into three. First, to describe the effective sentence mastery of the first year students at SMK Negeri 2 Padang. Second, to describe the writing skills of a exposition of the first year students at SMK Negeri 2 Padang. Third, to describe the contribution of the effective sentence mastery into the writing skills of a exposition text made by the first year students at SMK Negeri 2 Padang. The design of this research was quantitative with a descriptive method. Then, this study also was a correlational design. The population of this study was the first year students at SMK Negeri 2 Padang for about 498 students. The sample of this study was taken by using a proportional random sampling technique (15%), which was 70 students. The data of this study were the results of effective sentence mastery and the results of the writing skill of a exposition text. The instrument of this study was an objective test to measure effective sentence mastery and performance tests to measure expositon text. There were several results of this study. First, the effective sentence mastery of the first year students at SMK Negeri 2 Padang was in Good qualifications (B). Second, the writing skills of a exposition of the first year students at SMK Negeri 2 Padang was in a Good qualification (B). Third, describe the effective sentence mastery contributed 82,00% to the exposition text writing skills of the first year students of SMK Negeri 2 Padang. Kata Kunci: kontribusi, penguasaan kalimat efektif, keterampilan menulis teks eksposisi